Sounds - Arnold, Tedd. (New York, N.Y. : Little Simon, 1985)
A collection of seven nursery rhymes introducing the animal sounds of the pig, cat, rooster, and other animals. On board pages.
Cover title.
Keywords: Nursery rhymes; Children's poetry; Nursery rhymes; Animal sounds